Costs of hospitalizations for cerebrovascular accident in the southeast region of Brazil from 2013 to 2022. An ecological study (Research, Society and Development, 2024)
Objective: To identify the costs of hospitalizations due to cerebrovascular accidents in the Southeast Region from 2013 to 2022. Methodology: A descriptive ecological study conducted in November 2023, through data collection from the Informatics Department of the Unified Health System (DATASUS). Variables related to hospital admissions and costs were used, stratified by gender, age group, and year of admission. Results: It was found that the total amount spent was 825,698,291.92 and the year with the most hospitalizations was 2022. The sociodemographic profile showed that the number of hospitalizations in men was higher compared to women, and the age group with the most hospitalizations was the elderly between 60-69 years, which demonstrates higher economic consumption in these populations. Conclusion: According to the study, it was evident that cerebrovascular accidents demand high costs. Furthermore, it is crucial to identify these more vulnerable populations to facilitate strategies aimed at reducing expenses for this pathology.